Menemukan Berbagai Upaya Guru Bimbingan dan Konseling dalam Membantu Adaptasi Santri Baru pada Perbedaan Bahasa di Pesantren - Rizka Tri Loama; Agus Basuki (Journal of Current Research in Management, Policy, and Social Studies, 2024)
Adaptation is an effort to adapt to the environment. Adaptation cannot occur quickly, because students' adjustment to a new environment requires time and process. The purpose of the adaptation is as an effort for students to be able to interact with each other so that a good relationship is built between students and so that students are able to adapt to culture and language and can also communicate well with other students and can also adapt to existing regulations. at the Islamic boarding school. This research aims to examine the various efforts of guidance and counseling teachers to help new students adapt to language differences in Islamic boarding schools, what efforts guidance and counseling teachers can make to help students adapt to these language differences. This research method was carried out by literature study. Various techniques and methods that guidance and counseling teachers can use to help students overcome their problems have been described in this research. It is hoped that the description presented in this research will be useful and can help guidance and counseling teachers solve problems experienced by students who have problems adapting due to language differences.